MAKNA GANDA (HOMONIM) DALAM TUTURAN BAHASA JAWA DIALEK MOJOKERTO: ANALISIS SEMANTIK DI DESA SIDOREJO, KECAMATAN JETIS - Tisya Rexa Oktavia; Rani Jayanti (CV. Denasya Smart Publisher, 2025)
This study examines the double meaning of words (homonyms) in the Javanese language using the Mojokerto dialect as part of an analysis of the meaning and use of local language in social interactions in Sidorejo Village, Jetis District. The existence of homonyms is important because it shows that one way of speaking can have different meanings depending on its use, which is closely related to how speakers understand and interpret conversations in everyday life. The purpose of this study is to identify the types of homonyms, homophones, and homographs that appear in speech, as well as to explain their semantics and pragmatics. The method used was qualitative descriptive, with data collected through semi-structured interviews with native speakers of the Mojokerto dialect. A total of 13 speech data were collected and analyzed by considering their meanings and usage. The results showed that there were eight types of homonyms, five types of homographs, and no homophones were found in the speech of the community. The analysis shows that this diversity of meaning not only reflects the richness of the Mojokerto dialect vocabulary, but also reflects the relationship between language and social practices in the local community. This study confirms that understanding context is very important in interpreting meaning, and this is the basis for efforts to preserve local languages in an era of change.